Proceedings of the 24th ACM SIGKDD International Conference on Knowledge Discovery &Amp; Data Mining 2018
DOI: 10.1145/3219819.3220060
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Wavelet Decomposition Network for Interpretable Time Series Analysis

Abstract: Recent years have witnessed the unprecedented rising of time series from almost all kindes of academic and industrial fields. Various types of deep neural network models have been introduced to time series analysis, but the important frequency information is yet lack of effective modeling. In light of this, in this paper we propose a wavelet-based neural network structure called multilevel Wavelet Decomposition Network (mWDN) for building frequency-aware deep learning models for time series analysis. mWDN pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 163 publications
(70 citation statements)
references
References 38 publications
(44 reference statements)
0
70
0
Order By: Relevance
“…In the CNN‐based TM prediction model, there are two convolution layers, where the first has 8 filters with size (3, 3) and the second has four filters with size (3, 3). Long short‐term memory, which has been used in many TM prediction tasks . In the LSTM‐based TM prediction model, there are two LSTM layers, each of which has 200 units. Wavelet decomposition‐based LSTM, which has been shown to be superior to RNN/LSTM in temporal modeling capability . In the wLSTM‐based TM prediction model, we first use Daubechies 4 wavelet to decompose original TM series into four levels TM subseries.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…In the CNN‐based TM prediction model, there are two convolution layers, where the first has 8 filters with size (3, 3) and the second has four filters with size (3, 3). Long short‐term memory, which has been used in many TM prediction tasks . In the LSTM‐based TM prediction model, there are two LSTM layers, each of which has 200 units. Wavelet decomposition‐based LSTM, which has been shown to be superior to RNN/LSTM in temporal modeling capability . In the wLSTM‐based TM prediction model, we first use Daubechies 4 wavelet to decompose original TM series into four levels TM subseries.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
“…Kong et al applied the machine learning technologies to big data‐driven traffic flow prediction problem and constructed a novel prediction network with the LSTM model for performance measurement system. Combined with the ability of wavelet multiscale analysis, Wang et al demonstrated that wavelet decomposition‐based LSTM (wLSTM), in which wavelet decomposition was employed as a feature engineering tool before deep modeling, could be superior to traditional RNN and LSTM for time‐series forecasting tasks. However, these LSTM‐based models often ignore local spatial dependencies among multivariate time series.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…A natural follow-up question is: what kind of stocks would be selected as winners by AlphaStock? To answer this question, we propose a sensitivity analysis method [1,25,26] to interpret how the history features of a stock influence its winner score in our model.…”
Section: Model Interpretationmentioning
confidence: 99%